Reduction of bitter taste receptor gene family in folivorous colobine primates relative to omnivorous cercopithecine primates - Min Hou; Muhammad Shoaib Akhtar; Masahiro Hayashi; Ryuichi Ashino; Akiko Matsumoto-Oda; Takashi Hayakawa; Takafumi Ishida; Amanda D. Melin; Hiroo Imai; Shoji Kawamura (Primates, 2024)
Bitter taste perception is important in preventing animals from ingesting potentially toxic compounds. Whole-genome assembly (WGA) data have revealed that bitter taste receptor genes ( TAS2R s) comprise a multigene family with dozens of intact and disrupted genes in primates. However, publicly available WGA data are often incomplete, especially for multigene families. In this study, we employed a targeted capture (TC) approach specifically probing TAS2R s for ten species of cercopithecid primates with diverse diets, including eight omnivorous cercopithecine species and two folivorous colobine species. We designed RNA probes for all TAS2R s that we modeled to be intact in the common ancestor of cercopithecids (“ancestral-cercopithecid TAS2R gene set”). The TC was followed by short-read and high-depth massive-parallel sequencing. TC retrieved more intact TAS2R genes than found in WGA databases. We confirmed a large number of gene “births” at the common ancestor of cercopithecids and found that the colobine common ancestor and the cercopithecine common ancestor had contrasting trajectories: four gene “deaths” and three gene births, respectively. The number of intact TAS2R genes was markedly reduced in colobines (25–28 detected via TC and 20–26 detected via WGA analysis) as compared with cercopithecines (27–36 via TC and 19–30 via WGA). Birth or death events occurred at almost every phylogenetic-tree branch, making the composition of intact genes variable among species. These results show that evolutionary change in intact TAS2R genes is a complex process, refute a simple general prediction that herbivory favors more TAS2R genes, and have implications for understanding dietary adaptations and the evolution of detoxification abilities.

The sticky tasty: the nutritional content of the exudativorous diet of the Javan slow loris in a lowland forest - Tungga Dewi; Muhammad Ali Imron; Ganis Lukmandaru; Katherine Hedger; Marco Campera; K. A. I. Nekaris (Primates, 2022)

Why do people visit primate tourism sites? Investigating macaque tourism in Japan and Indonesia - Asmita Sengupta; Kanthi Arum Widayati; Yamato Tsuji; Risma Yanti; Muhammad Fadli Rahman; Nagarathna Balakrishna; Sindhu Radhakrishna (Primates, 2021)

Is Malaysia’s banded langur, Presbytis femoralis femoralis, actually Presbytis neglectus neglectus? Taxonomic revision with new insights on the radiation history of the Presbytis species group in Southeast Asia - Muhammad Abu Bakar Abdul-Latiff; Hanisah Baharuddin; Pazil Abdul-Patah; Badrul Munir Md-Zain (Primates, 2019)

Comparison of fecal preservation and extraction methods for steroid hormone metabolite analysis in wild crested macaques - Gholib Gholib; Michael Heistermann; Muhammad Agil; Iman Supriatna; Bambang Purwantara; Taufiq Purna Nugraha; Antje Engelhardt (Primates, 2018)

Validation of a field-friendly extraction and storage method to monitor fecal steroid metabolites in wild orangutans - Taufiq Purna Nugraha; Michael Heistermann; Muhammad Agil; Bambang Purwantara; Iman Supriatna; Gholib Gholib; Carel P. van Schaik; Tony Weingrill (Primates, 2017)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)